DETERMINASI KESIAPAN KERJA MAHASISWA AKUNTANSI - Natalia Natalia; Aris Eddy Sarwono (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
Accounting students’ job readiness is a crucial issue in facing the demands of an increasingly digitalized professional world. This study evaluates the role of Accounting Information Systems (AIS) use, accounting competencies, and digital literacy in shaping student job readiness. A quantitative approach using survey method was applied to 153 accounting students at private universities in Surakarta City who had taken courses related to Accounting Information Systems. Data were analyzed using multiple linear regression. The study findings indicate that these three variables significantly contribute to job readiness. Individually and collectively, mastery of technical competencies and digital skills is positively correlated with increased student readiness to enter the workforce. This underscores the importance of integrating accounting skills and technological literacy into yhe learning process. This study was limited to accounting students at privet universities in Surakarta City, so the results cannot be broadly generalized to the entire accounting student population